Breaking the Poverty Cycle: Impact of Social Assistance on Intergenerational Poverty - Felicia Putri Anggrasari; Muhammad Hanri (The Journal of Indonesia Sustainable Development Planning, 2025)
The intergenerational transmission of poverty is a structural problem in Indonesia. The transmission of poverty presents a considerable barrier to poverty eradication and requires concerted government intervention. Social assistance plays a vital role in strengthening household income, fostering better outcomes for children, and addressing the long-term transmission of poverty from one generation to the next. Despite its potential, this program also faces dependency and suboptimal utilization, which limit its impact on enhancing children’s human capital. Therefore, this research seeks to examine the impacts of social assistance on intergenerational poverty. This research primarily utilizes IFLS data from 2007 to 2014 using the method of propensity score matching. The findings indicated that parents receiving social assistance had a 19.4% point decrease in the likelihood of their children experiencing poverty. The Family Hope Program (PKH), as a conditional cash transfer, has the most substantial impact on alleviating child poverty. These findings provide important lessons for designing policies to achieve the Sustainable Development Goals (SDGs), particularly Goal 1 and Goal 10.